BACHELOR DEGREE PROGRAMS IN INTERNATIONAL RELATIONS AND REGIONAL STUDIES: A COMPETENCE-BASED APPROACH TO PROFESSIONAL TRAINING OF STUDENTS IN FOREIGN LANGUAGES - L. G. Kuzmina (Vestnik MGIMO-Universiteta)
The paper is devoted to the problem of devising a new ESP curriculum for university students within the framework of Federal State Educational Standards of Higher Education. The necessity to introduce innovations into foreign language teaching at universities is fore grounded. It is claimed that in spite of some ambiguity in specifying the students’ competence in foreign languages put forward in the Standards, it is possible to design an effective educational curriculum for this university subject. It is proved that this can be realized if a competence-oriented approach is implemented. The process of designing a new competence-based curriculum for foreign languages is being described. A model modular course in foreign languages for the university students majoring in Regional Studies is presented. Some strategies to further develop teaching foreign languages at universities are mentioned. It is also argued that the course under discussion has proved to be attractive for the university applicants, provides for the quality of language education and meets the needs of the regional business community in the specialists of this kind.